PERAN ORGANISASI MAHASISWA DALAM MENINGKATKAN MUTU PEMBELAJARAN KETERAMPILAN BERBAHASA ARAB - Faisal Hendra (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2018)
This article discusses how the student inter-organization of Arabic Literature study program in University of Al Azhar Indonesia takes role in enhancing quality of studying four Arabic language skills among students. This paper was focused on student organization mentoring pattern, type of program of activities formed by the organization, and the extent of students’ active participation as organization member in running the program. This paper used qualitative descriptive method. This paper proposed: (1) The concept of kinship became the foundation for managing the organization, especially in the way it is operated. (2) Program of activities in the organization varied in a sense that some programs were in line so to support the purpose of learning Arabic skill, while there were also programs that did not consider Arabic fluency. However, the latter was designed to harness students soft skills, and develop students talent and interest. (3) The extent of students participation seems adequate, although some students did not yet play their expected functional role as member of student organization.